Developing involvement during a programme of recovery research - Slade, Mike; Trivedi, Premila; Chandler, Ruth; Leamy, Mary (Emerald, 2016)
Purpose To consider the process of working with a Lived Experience Advisory Group (LEAP) and its outcomes in REFOCUS, a large 5 year programme of recovery research. Design Narrative reflections on the experience of working with LEAP were collected from five members and the Chair of LEAP, two REFOCUS researchers and the Principal Investigator (PI). These were synthesised to show both the process and outcomes of LEAP involvement in REFOCUS, and how involvement evolved organically over time. Findings Individual reflective accounts showed how working with LEAP impacted (to a greater or lesser extent) on each individual involved in the process, providing new insights and influencing, to varying degrees, the way in which they then worked with LEAP. Synthesis of the reflections showed how these changes impacted organically on LEAP's process of involvement, with a shift in LEAP's role from being purely consultative/advisory towards one which was much more about co-production, with LEAP proactively contributing to some aspects of Refocus in the later stages of the study. Practical implications We stress the importance of considering process as well as outcomes in Patient and Public Involvement (PPI), and make practical recommendations for improving both in future programmes of research. Originality/value This is the first empirical evaluation of user and carer involvement and its development during a large recovery research programme.